The lecture hall laboratory: Design of a field experiment for effectiveness analysis - Nofen, Barbara; Temmen, Katrin (2018 IEEE Global Engineering Education Conference (EDUCON))

Eine Untersuchung mit Studierenden über den Umgang mit ihrer Zeit - Friederici, D.-P. (Die Hochschullehre)

Design concept and prototype for an augmented reality based virtual preparation laboratory training in electrical engineering - Alptekin, Mesut; Temmen, Katrin (2018 IEEE Global Engineering Education Conference (EDUCON))
There have been numerous studies so far highlighting the potential of Augmented Reality (AR) in different educational domains and its impact on learners regarding their increased motivation, improved learning, concentration on the topic etc. Ever since high-end AR applications could be used on smartphones, this technology has become suitable to be used in many formal and informal learning environments and educational institutions, beginning with Arts courses in preschool over Biology, History, Chemistry, Physics etc. in K-12 and universities as well as in vocational schools ([1], [2]), e.g. for assembly trainings [3]. However, less research has been done regarding proper educational design principles and guides identifying the learning-promoting characteristics as to their efficacy in an AR environment ([1], [4]). Particularly there is a big lack for design concepts in the field of preparation and accompanying tools for laboratory work, since current studies are only extending real papers or books with additional links, videos or static 3D models (e.g. [5], [6]). Hence, this paper investigates and focuses at a design concept for mobile device based AR application (App) to acquire and deepen practical skills in dealing with electro-technical laboratory equipment and components. In a previous paper, the potentials and limitation of AR technology regarding engineering education with a special focus on laboratory work have been investigated to avoid common mistakes in the design concept.

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

Program FFlexCom — High frequency flexible bendable electronics for wireless communication systems - Meister, Tilo; Ellinger, Frank; Bartha, Johann W.; Berroth, Manfred; Burghartz, Joachim; Claus, Martin; Frey, Lothar; Gagliardi, Alessio; Grundmann, Marius; Hesselbarth, Jan; Klauk, Hagen; Leo, Karl; et al. (2017 IEEE International Conference on Microwaves, Antennas, Communications and Electronic Systems (COMCAS))

Beta Distributions and Sonine Integrals for Bessel Functions on Symmetric Cones - Rösler, Margit; Voit, Michael (Studies in Applied Mathematics)
Keywords: Applied Mathematics

On the Green Function and Poisson Integrals of the Dunkl Laplacian - Rösler, Margit; Graczyk, Piotr; Luks, Tomasz (Potential Analysis)
Keywords: Analysis

Emulation of polarization fluctuations in glass fibers caused by lightning strikes - Noé, Reinhold; Koch, Benjamin (Photonic Networks; 19th ITG-Symposium)

Joint Detection of Almost-Cyclostationary Signals and Estimation of Their Cycle Period - Horstmann, Stefanie; Ramírez, David; Schreier, Peter J. (IEEE Signal Process. Lett.)
We propose a technique that jointly detects the presence of almost-cyclostationary (ACS) signals in wide-sense stationary (WSS) noise and provides an estimate of their cycle period. Since the cycle period of an ACS process is not an integer, the approach is based on a combination of a resampling stage and a multiple hypothesis test, which deal separately with the fractional part and the integer part of the cycle period. The approach requires resampling the signal at many different rates, which is computationally expensive. For this reason we propose a filter bank structure that allows us to efficiently resample a signal at many different rates by identifying common interpolation stages among the set of resampling rates.

Approximate Asymptotic Distribution of Locally Most Powerful Invariant Test for Independence Complex Case - Xiao, Y-.H.; Huang, L.; Xie, J.; So, H. C. (IEEE Transactions on Information Theory)

LMPIT-inspired Tests for Detecting a Cyclostationary Signal in Noise with Spatio-Temporal Structure - Pries, Aaron; Ramírez, David; Schreier, Peter J. (IEEE Trans. Wirel. Commun.)

A degrees-of-freedom-achieving scheme for the temporally correlated MIMO interference channel with delayed CSIT - Rezaee, Mohsen; Schreier, Peter J. (IEEE Trans. Wireless Comm.)

Complete Model Selection in Multiset Canonical Correlation Analysis - Marrinan, T.; Hasija, Tanuj; Lameiro, C.; Schreier, P. J. (Proc. European Signal Process. Conf. (EUSIPCO))

Space‐time fractional Dirichlet problems - Baeumer, Boris; Luks, Tomasz; Meerschaert, Mark M. (Mathematische Nachrichten)
Keywords: General Mathematics

Improper Signaling for OFDM Underlay Cognitive Radio Systems - Soleymani, Mohammad; Lameiro, Christian; Schreier, Peter J.; Santamaría, Ignacio (Proc. IEEE Statistical Signal Processing Workshop (SSP))

Regularized lattice reduction-aided ordered successive interference cancellation for MIMO detection - Tong, J.; Guo, Q.; Xi, J.; Yu, Y.; Schreier, P. J. (Proc. IEEE Workshop on Statistical Signal Processing)

Improper Gaussian signaling for multiple-access channels in underlay cognitive radio - Lameiro, Christian; Santamaría, Ignacio; Schreier, Peter J. (IEEE Transactions on Communications)

Performance Analysis of Locally Most Powerful Invariant Test for Sphericity of Gaussian Vectors in Coherent MIMO Radar - Xiao, Y-.H.; Huang, L.; Zhang, J-.K.; Xie, J.; So, H. C. (IEEE Transactions on Vehicular Technology)

Information-Theoretic Analysis of a Family of Improper Discrete Constellations - Santamaria, Ignacio; Crespo, Pedro M.; Lameiro, Christian; Schreier, Peter J. (Entropy)

MODEL-ORDER SELECTION IN STATISTICAL SHAPE MODELS - Eguizabal, A.; Schreier, P. J.; Ramírez, D. (2018 IEEE 28th International Workshop on Machine Learning for Signal Processing (MLSP))